From chip-in-a-lab to lab-on-a-chip: a portable Coulter counter using a modular platform. (December 2018) - Dekker, Stefan; Isgor, Pelin; Feijten, Tobias; Segerink, Loes; Odijk, Mathieu
Abstract The field of microfluidics has been struggling to obtain widespread market penetration. In order to overcome this struggle, a standardized and modular platform is introduced and applied. By providing easy-to-fabricate modular building blocks which are compatible with mass manufacturing, we decrease the gap from lab-to-fab. These standardized blocks are used in combination with an application-specific fluidic circuit board. On this board, electrical and fluidic connections are demonstrated by implementing an alternating current Coulter counter. This multipurpose building block is reusable in many applications. In this study, it identifies and counts 6 and 11 μm beads. The system is kept in a credit card-sized footprint, as a result of in-house-developed electronics and standardized building blocks. We believe that this easy-to-fabricate, credit card-sized, modular, and standardized prototype brings us closer to clinical and veterinary applications, because it provides an essential stepping stone to fully integrated point -of -care devices. Microfluidics: standardized and modular devices A coulter counter based on a standardized modular platform using microfluidic building blocks provides the opportunity for low-cost and portable microfluidic devices. A drawback of current microfluidic devices is that they often have a large physical footprints, and make use of multiple non-standardized components. Now, a team led by Mathieu Odijk at University of Twente in the Netherlands demonstrates a credit card-sized microfluidic device produced from modular building blocks on a fluidic circuit board, providing a standardized and fixed-footprint platform for transferring microfluidics from lab to industry. Moreover, reusable and standardized parts reduce the time for device design and fabrication. As proof of concept they demonstrate an alternating current coulter counter for micron-sized beads.